Diversity of Araliaceae in Sulasih Talang Nature Reserve, West Sumatra and its acclimatization - HARY WAWANGNINGRUM; DWI MURTI PUSPITANINGTYAS (Biodiversitas Journal of Biological Diversity, 2008)
Sulasih Talang Nature Reserve is a conservation area in West Sumatra Province, which contains high diversity of plants including Araliaceae. Araliaceae mostly consist of attractive plants which have potentiallity as ornamental plants. The aim of this research is to record the diversity of Araliaceae in Sulasih Talang Nature Reserve. The result of the study indicates that there are, species of Araliaceae found in Sulasih Talang Nature Reserve, which are : Arthrophyllum diversifolium, Brassaiopsis glomerulata, Brassaiopsis sumatrana var. variaefolia, Macropanax dispermus, Schefflera elliptica, S. farinosa, S. lucescens, S. scandens, Schefflera sp., and Trevesia beccarii, in which Bogor Botanic Garden collected 6 species of them, i.e.: Brassaiopsis glomerulata, Brassaiopsis sumatrana var. variaefolia, Macropanax dispermus, Schefflera elliptica, S. scandens, Schefflera sp. Most of the collections are successfully acclimated in the gardens.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Araliaceae, Sulasih Talang Nature Reserve, acclimatization